PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MEREK ERIGO DI KAB. GRESIK - Arif Radika (ECONOMOS, 2022)
The purpose of this study was to determine the effect of brand image, price and product quality on purchasing decisions on the Erigo brand. The data used are data from the results of distributing online questionnaires to samples that match the criteria and information from reference results. This study uses the Statistical Program for Social Science (SPSS) 24 as an analytical tool and a Likert scale. The population used is the people of Gresik Regency, East Java who have bought Erigo brand products. The sampling technique in this research is purposive sampling. The research sample is the people of Gresik Regency, East Java who have bought Erigo brand products with 50 men and 50 women. This study uses a quantitative approach (multiple linear regression). The results showed that the Brand Image variable had a significant effect simultaneously with the Price and Product Quality variables, but partially had an insignificant effect on the Erigo product Purchase Decision variable. Meanwhile, the price and product quality variables have a positive and significant effect, either partially or simultaneously on the variable purchasing decisions for Erigo products.